Answers

2015-08-04T20:11:46+08:00
 It works like this:
First, I put the loose number on the other side of the equation:x2 – 4x – 8 = 0 
x2 – 4x = 12 
Then I look at the coefficient of the x-term, which is –4 in this case. I take half of this number (including the sign), giving me –2. Then I square this value to get +4, and add this squared value to both sides of the equation:x2 – 4x + 4 = 8 + 4 
x2 – 4x + 4 = 16
This process creates a quadratic that is a perfect square, and factoring gives me:(x – 2)2 = 16

tapos, extract the sq. root of both sides:)

x=6, -2
0